A cross-cultural evaluation of Bostick's (1992) library anxiety scale: Investigating the scale's psychometric properties in a Malaysian university library environment - Karim, N.H.A.; Ansari, N.A. (2010)
Sharon L Bostick's (1992) Library Anxiety Scale has been widely used to assess library anxiety among library users. Little psychometric effort was undertaken to assess the scale's psychometric properties in an environment where English is not the native language of the library users. This study was an attempt to cross-culturally validate the scale in a Malaysian university library environment where the population's native language is not English. A 49-item modified version of Bostick's (1992) Library Anxiety Scale was tested among 367 students drawn randomly from a population of 8,432 undergraduate students. The instruments were administered during classroom hours using a self-reported questionnaire. An 84% return rate was achieved in which the questionnaires that were returned were found to be usable. The findings revealed that a 5-factor solution was found which corresponded to the five factors as found by Bostick's (1992) pioneering psychometric effort on library anxiety. The factor ``barriers with staff'' explained the greatest proportion of variance in the library anxiety construct which is consistent with previous studies on library anxiety. The overall scale as well as each of the five sub-scales was submitted to an internal reliability assessment using Cronbach's internal reliability coefficient alpha. With the exception of the modified sub-scale ``comfort with library technology'' all the four sub-scales as well as the overall scale were found to have satisfied the 0.70 criteria as recommended by Nunnally and Bernstein (1994). As such the findings were found to be consistent with previous studies that found the scale to be valid as well as internally reliable. More psychometric efforts are needed before the scale can be said to be a useful instrument in assessing library anxiety among Malaysian university library users. A Malay version of Bostick's (1992) scale would have to be tested before any sound conclusions can be made about the scale's psychometric soundness and stability in an environment where English is not the native language.